Indirect measurements of the composition of ultrafine particles in the Arctic late-winter - Myers, Deanna; Smith, James (Zenodo, 2022)
We present indirect measurements of size-resolved ultrafine particle composition conducted during the Ocean–Atmosphere–Sea Ice–Snowpack (OASIS) Campaign in Utqiagvik, Alaska, during March 2009. This study focuses on measurements of size-resolved particle hygroscopicity and volatility measured over two periods of the campaign. During a period that represents background conditions in this location, particle hygroscopic growth factors (HGF) at 90% relative humidity ranged from 1.45-1.51, which combined with volatility measurements suggest a mixture of ~30% ammoniated sulfates and ~70% oxidized organics. Two separate regional ultrafine particle growth events were also observed during this campaign. Event 1 coincided with elevated levels of H2SO4 and solar radiation. These particles were highly hygroscopic (HGF=2.1 for 35 nm particles), but were almost fully volatilized at 160 °C. The air masses associated with both events originated over the Arctic Ocean. Event 1 was influenced by the upper marine boundary layer (200-350 m AGL), while Event 2 spent more time closer to the surface (50-150m AGL) and over open leads, suggesting marine influence in growth processes. Event 2 particles were slightly less hygroscopic (HGF=1.94 for 35nm and 1.67 for 15nm particles), and similarly volatile. We hypothesize that particles formed during both events contained 60-70% hygroscopic salts by volume, with the balance for Event 1 being sulfates and oxidized organics for Event 2. These observations suggest that primary sea spray may be an important initiator of ultrafine particle formation events in the Arctic late-winter, but a variety of processes may be responsible for condensational growth. Data information is contained within the read me files accompanying each set. Please read carefully. Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: